THE ANALYSIS ON THE READINESS OF ENGLISH TEACHERS IN IMPLEMENTING AUTHENTIC ASSESSMENT IN SENIOR HIGH SCHOOLS - Dharma, I Putu Suyoga; Adiwijaya, Pande Agus (Universitas Pendidikan Ganesha, 2019)
This research aimed at discovering the readiness of English teachers in implementing authentic assessment in Senior High Schools which would implement curriculum 2013 in Bangli Regency. This is an evaluative study with discrepancy analysis approach proposed by Provust. Here, the idealimplementation of authentic assessment was compared to the real implementation by the English teachers. Two English teachers in SMAN 2 Bangli and SMAN 1 Tembuku were taken as the subjects of the research. The objects involved planning, executing, and reporting of authentic assessment in the form of portfolio, performance, project, and self-assessment. To collect the data, three rubrics for planning, executing, and reporting with Likert scale were used. This research discovers: 1) interms of planning, the teachers’ readiness is classified into average, 2) in terms of execution, the teachers’ readiness is classified into not ready, and 3) in terms of reporting, the teachers’ readiness is classified into not ready. There were three main problems faced by the teachers in implementingauthentic assessment, namely: a) lack of authentic assessment knowledge, b) lack of experience in designing authentic assessment, and c) lack of sharing from friends who get workshop about authentic assessment. From this research, it is suggested that a) teachers to join workshop and toread references about authentic assessment, and b) government should held more workshop about authentic assessment.